Controlling the atomic distribution in PtPd nanoparticles: thermal stability and reactivity during NO abatement. Issue 15 (31st March 2017) - Schafer, D.; Castegnaro, M. V.; Gorgeski, A.; Rochet, A.; Briois, V.; Alves, M. C. M.; Morais, J.
Abstract : In situ X-ray absorption spectroscopy and mass spectrometry measurements were employed to simultaneously probe the atom specific short range order and reactivity of Pd and PtPd nanoparticles towards NO decomposition at 300 °C. Abstract : In situ X-ray absorption spectroscopy and mass spectrometry measurements were employed to simultaneously probe the atom specific short range order and reactivity of Pd and PtPd nanoparticles towards NO decomposition at 300 °C. The nanoparticles were synthesized by a well controlled, eco-friendly wet chemical reduction of metal salts and later supported on activated carbon. Particularly for the bimetallic PtPd samples, distinct atomic arrangements were achieved using a seeding growth method, which allowed producing a random nanoalloy, or nanoparticles with Pt- or Pd-rich core. X-ray photoelectron spectroscopy, transmission electron microscopy, and X-ray diffraction provided additional insights on their electronic, morphological and long range order structural properties. The results revealed that the higher the thermal induced atomic migration observed within the nanoparticles during thermal treatments, the least were their reactivity for NO abatement.